CHARACTERISTIC OF SEDIMENT AT LEKOK COASTAL WATERS, PASURUAN REGENCY, EAST JAVA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Sedimentation is one of the dynamics that occur in coastal areas to determine the condition of the coast. Lekok coastal water is one of the open water areas that have very fluctuating dynamics in coastal changes. The structural study of sediment distribution conducted in this location is used to provide information about the process of transportation and sedimentation based on the distribution of sediment grain size. This study aims to determine the horizontal grain sediment size in the Lekok coastal waters. This research was conducted at nine sampling points by sampling in the form of primary sediments randomly using the grab sampler method. Furthermore, further analysis is done by the gravimetric method. Based on the results of the study note that sediments characteristic in Lekok coastal water are generally dominated by three types of sediments, namely: sandy loam, loam, and silt loam. Sorting values ​​are in a well-sorted to the moderately well-sorted condition where the sediment conditions are well sorted. The skewness value is skewed positively, where the value indicates a positive skewed sedimentary condition. The value of kurtosis is in the leptokurtic condition where the sediment from station 1 to station 9 is homogeneous.